2020
DOI: 10.1002/nop2.678
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety. Factors for and perceived consequences of nursing errors by nursing staff in home care services

Abstract: Aim To identify factors for and perceived consequences of nursing errors by nursing staff in home care services in correlation with qualification, work experience, working hours and trainings. Background Patient safety has increasingly been brought into focus of politics and care practices over the past few years. However, little evidence has been provided yet on nursing errors in out‐of‐hospital settings. Design A cross‐sectional study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
1
10
0
3
Order By: Relevance
“…Adverse events in nursing care are clinically defined as unanticipated events during care that may cause the patient to receive physical or psychological harm, including unnatural accidents such as a patient falling out of bed, wandering, falling, aspiration, and dislodging a blood or fluid line during hospitalization [ 10 , 11 ]. A relevant report by the World Health Organization (WHO) [ 12 ] showed that the chance of accidental injury to patients treated in developed countries was 10%, and about 40% of these injured patients were caused by nursing accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events in nursing care are clinically defined as unanticipated events during care that may cause the patient to receive physical or psychological harm, including unnatural accidents such as a patient falling out of bed, wandering, falling, aspiration, and dislodging a blood or fluid line during hospitalization [ 10 , 11 ]. A relevant report by the World Health Organization (WHO) [ 12 ] showed that the chance of accidental injury to patients treated in developed countries was 10%, and about 40% of these injured patients were caused by nursing accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Ao identificar os fatores de risco ligados aos resultados do tratamento, deve-se implementar ou adaptar planos de cuidados e gerenciar os erros. (3) Diante disso, vislumbrou-se a implementação do NSP para padronizar os processos, propor uma cultura de segurança na equipe integrante do serviço e identificar os erros, intervindo em melhorias das práticas em exercício.…”
Section: Discussionunclassified
“…São necessárias práticas para identificar e gerenciar os erros que impactem na segurança da atenção em saúde, além disso, atos como treinamento e capacitação dos profissionais são instituídos para que venham a contribuir para atingir um padrão de alta qualidade associado à segurança do paciente. (3) Sendo assim, o programa visa uma gestão de riscos voltada à qualidade dos cuidados ofertados e à implementação da cultura de segurança no serviço. Com o propósito de instituir princípios e diretrizes que subsidiem os processos organizacionais do serviço para a promoção e o desenvolvimento de ações direcionados aos pacientes.…”
Section: Introductionunclassified
“…However, there is no standardized reporting system [ 9 ], and it is possible that all events have not been reported. For patient safety in home care services, it is important to have regular error management training [ 10 ]. Home-visiting nursing agencies in Japan provide training in the prevention of medical incidents and produce incident reports.…”
Section: Introductionmentioning
confidence: 99%